2021
DOI: 10.3389/fcell.2021.770899
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeraniol Restores Zoledronic Acid-Induced Efferocytosis Inhibition in Bisphosphonate-Related Osteonecrosis of the Jaw

Abstract: Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a severe side effect of long-term administration of bisphosphonates such as zoledronic acid (ZA), but its pathogenesis remains unclear. Impairment of the clearance of apoptotic cells (termed “efferocytosis”) by ZA may be associated with the pathogenesis of BRONJ. The aim of this study was to investigate whether ZA might inhibit macrophage efferocytosis and promote osteocytic apoptosis, and the underlying mechanisms responsible for the disturbing balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In the study of Chen et al, male C57BL/6J mice (4-week-old) were given zoledronate (250 μg/kg, i. p.) twice a week and their first maxillary molar were extracted 1 week after zoledronate treatment. GGOH (250 μg/kg) was administered together with zoledronate after tooth extraction for 4 weeks ( Chen et al, 2021 ). Zoledronate stimulates osteocyte and pre-osteoblast apoptosis in mice and suppressed efferocytosis of macrophages on apoptotic cells ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of Chen et al, male C57BL/6J mice (4-week-old) were given zoledronate (250 μg/kg, i. p.) twice a week and their first maxillary molar were extracted 1 week after zoledronate treatment. GGOH (250 μg/kg) was administered together with zoledronate after tooth extraction for 4 weeks ( Chen et al, 2021 ). Zoledronate stimulates osteocyte and pre-osteoblast apoptosis in mice and suppressed efferocytosis of macrophages on apoptotic cells ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…GGOH (250 μg/kg) was administered together with zoledronate after tooth extraction for 4 weeks ( Chen et al, 2021 ). Zoledronate stimulates osteocyte and pre-osteoblast apoptosis in mice and suppressed efferocytosis of macrophages on apoptotic cells ( Chen et al, 2021 ). GGOH reverse the negative effects of zoledronate on efferocytosis by restoring Rac1 homeostasis and shuttling Rac1 at the cellular membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the role of Rac1 on bone homeostasis in GIOP has rarely been reported. Some studies have suggested that imbalance or abnormal function of Rac1 will negatively impact the skeletal system, regardless of whether it is up-regulated or down-regulated ( Chen et al, 2021 ; Mäkitie et al, 2021 ). In this study, SPM induced the expression of Rac1, suppressing bone resorption and facilitating bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have recently shown that GGOH could preserve a pool of viable MSCs with osteogenic potency against ZA and suggested GGOH as a promising agent for BRONJ prevention A systemic application of GGOH may interfere with the therapeutic benefit of N-BPs at the other bony sites, while local irrigation or delivery without a control release carrier requires nonpractically frequent GGOH applications. A well sustained release system for local delivery of GGOH may be more practical to prevent BRONJ and promote better jawbone healing after bony surgery.…”
Section: Introductionmentioning
confidence: 99%